Machine learning to detect and classify engine and car faults through sound - Mennani, Baha Eddine (Université of eloued جامعة الوادي, 2025)
عد تشخيص أعطاب المحركات من المهام الحيوية في صيانة المركبات، وقد فتحت تقنيات الذكاء الاصطناعي أفاقا جديدة نحو وسائل فعالة وغير تدخلية للكشف عن هذه الأعطاب في هذا العمل، تم تقديم منهجية شاملة لتصنيف أعطاب المحركات باستخدام الإشارات الصوتية ونماذج التعلم الآلي والتعلم العميق. تم تسجيل أصوات محركات سليمة ومعطوبة في ظروف واقعية، وتم استخراج خصائص MFCC والمخططات الطيفية منها. ثم تم تدريب وتقييم عدة نماذج، من بينها K-NN و في سيناريوهات تصنيف ثنائي ومتعدد الفئات لكل LSTM و CNN و ANN XGBoost Random Forest من محركات البنزين والديزل أظهرت النتائج كفاءة عالية للتحليل الصوتي المعتمد على الذكاء الاصطناعي، خاصة باستخدام نماذج CNN و LSTM كما تم تطوير نظام خفيف باستخدام TFLite لتوفير تشخيص فوري عبر تطبيق هاتف محمول. Engine fault diagnosis is a critical task in automotive maintenance, and recent advances in artificial intelligence have enabled new possibilities for noninvasive and efficient detection methods. This work presents a comprehensive approach for detecting and classifying engine faults using sound signals combined with machine learning (ML) and deep learning (DL) models. Real world engine audio recordings, both healthy and faulty, were collected and processed to extract MFCC and spectrogram features. Multiple models — Random Forest, XGBoost, ANN, CNN, and LSTM — including KNN, were trained and evaluated under both binary and multiclass classification scenarios for gasoline and diesel engines. The results demonstrate the potential of AIbased acoustic analysis as a reliable tool for early fault detection, with CNN and LSTM models showing superior performance in complex classification tasks. A lightweight TFLitebased system was also implemented for real mobile diagnosi
Internat of things and Cybersecurtity
Keywords: تشخيص أعطاب المحركات تعلم الي تعلم عميق CNN MFCC تصنيف صوتي، تحليل صوتي TFLite، تشخيص محمول.; Engine fault diagnosis; machitime ne learning; deep learning; MFCC; CNN; sound classification; acoustic analysis; TFLite; mobile diagnosis.